2018
DOI: 10.1111/infa.12236
|View full text |Cite
|
Sign up to set email alerts
|

Just Before I Recognize Myself: The Role of Featural and Multisensory Cues Leading up to Explicit Mirror Self‐Recognition

Abstract: Leading up to explicit mirror self‐recognition, infants rely on two crucial sources of information: the continuous integration of sensorimotor and multisensory signals, as when seeing one's movements reflected in the mirror, and the unique facial features associated with the self. While visual appearance and multisensory contingent cues may be two likely candidates of the processes that enable self‐recognition, their respective contribution remains poorly understood. In this study, 18‐month‐old infants saw sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The process of relating stimuli to the self should not be considered as an isolated phenomenon, but rather as embedded in a larger process depending on the environmental context ( Salone et al, 2016 ). It has been suggested that 18-months-old infants who were coded as non-recognizers at the mirror-test task spent more time looking at the picture of their own face compared to the other-face, suggesting that before the onset of mirror self-recognition, featural information about the self might are more relevant in the process of recognizing one’s face, compared to multisensory cues ( Filippetti and Tsakiris, 2018 ). Subortical-cortical midline structures (SCMS) are brain areas that enable self-related processing (SRP; Northoff and Panksepp, 2008 ).…”
Section: Pleasure and Affects: Psychoanalytic And Neuropsychoanalyticmentioning
confidence: 99%
“…The process of relating stimuli to the self should not be considered as an isolated phenomenon, but rather as embedded in a larger process depending on the environmental context ( Salone et al, 2016 ). It has been suggested that 18-months-old infants who were coded as non-recognizers at the mirror-test task spent more time looking at the picture of their own face compared to the other-face, suggesting that before the onset of mirror self-recognition, featural information about the self might are more relevant in the process of recognizing one’s face, compared to multisensory cues ( Filippetti and Tsakiris, 2018 ). Subortical-cortical midline structures (SCMS) are brain areas that enable self-related processing (SRP; Northoff and Panksepp, 2008 ).…”
Section: Pleasure and Affects: Psychoanalytic And Neuropsychoanalyticmentioning
confidence: 99%
“…Motor knowledge and proto-representations of the body seem to be forming already during pre-natal developmental stages (Zoia et al, 2007). Paradigms for measuring body awareness and agency attribution in infants (Filippetti et al, 2014;Filippetti and Tsakiris, 2018), as well as in adults (Shergill et al, 2003;Ehrsson et al, 2004), can be also found in the literature. As mentioned above, caregiver-infants close embodied relationship seems to support the development of primitive forms of a sense of self (Ciaunica and Fotopoulou, 2017;Ciaunica and Crucianelli, 2019).…”
Section: Languagementioning
confidence: 99%
“…Therefore, nonconceptual mental-state-like representations from our infancy do not disappear, but rather account for the efficiency and automaticity of our mental state ascriptions by adults [6]. Moreover, infants who have mastered a robust enough representation of themselves can more easily switch between being attending to others and attending to themselves [7].…”
Section: Introductionmentioning
confidence: 98%